Simulation of an electrolytic bath for electrodeposition of multilayer shielding coatings - E. A. Dolmatova; A. D. Dayanov; T. N. Ostanina (Chimica Techno Acta)
In the work galvanic bath of Cu/(Ni+Cu) multilayer shielding coatings formation from an acetate electrolyte containing 0,03 mol/L of CuAc2, 0,3 mol/L of NiAc2 and 1,66 mol/L of acetic acid. According to the results of polarization studies values of coatings deposition pulse mode current density have been chosen and current efficiency of copper and nickel during deposition of Cu-Ni alloy has been determined. To ensure a constant formulation of the electrolyte it has been proposed to use insoluble anodes made of stainless steel and continuous circulation of the electrolyte. The scheme of steams enabling the adjustment of the solution formulation with the use of an additional collecting vessel has been developed. The formulation of the correcting stream continuously fed into the collecting vessel has been calculated.